Singularities of differentiable maps : monodromy and asymptotics of integrals - Arnold, V I; Arnold, V I; Vachenko, A N; Gusein-Zade, S M (Boston, Birkhuser, 2012)
The present volume is the second in a two-volume set entitled Singularities of Differentiable Maps. While the first volume, subtitled Classification of Critical Points and originally published as Volume 82 in the Monographs in Mathematics series, contained the zoology of differentiable maps, that is, it was devoted to a description of what, where, and how singularities could be encountered, this second volume concentrates on elements of the anatomy and physiology of singularities of differentiable functions. The questions considered are about the structure of singularities and how they function.
References 461-488p.; Subject Index 489-492p.
Keywords: Differentiable mapping; Singularities; Mathematics